Association between retinal vasculature and muscle mass in older people. Issue 3 (November 2015) - Sumukadas, Deepa; McMurdo, Marion; Pieretti, Ilaria; Ballerini, Lucia; Price, Rosemary; Wilson, Peter; Doney, Alex; Leese, Graham; Trucco, Emanuele
Highlights Sarcopenia may be linked to cardiovascular disease and arterial stiffness. We found sarcopenia was not associated with retinal vasculature size. As anticipated larger muscle mass was associated with greater muscle strength. Unexpectedly we found larger muscle mass associated with smaller retinal artery size.